How to understand the word “tolerance”? - Jurayeva M.M.; Rakhmonova Zébo (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article offers a general overview of the lexical range of the word tolerance, its place in fiction, and its expression in the stories of Victor Hugo. Children's literature is used here to induce discussions about the idea of tolerance in two classes of 9-10 year old pupils.